Prognostic Implications of Left Ventricular Global Longitudinal Strain in Patients With Surgically Treated Mitral Valve Disease and Preserved Ejection Fraction - Lee, Seon Hwa; Lhagvasuren, Purevjargal; Seo, Jiwon; Cho, Iksung; Kim, Dae-Young; Hong, Geu-Ru; Ha, Jong-Won; Shim, Chi Young (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study investigated whether left ventricular (LV) global longitudinal strain (LV-GLS), as an LV function parameter less affected by mitral valve (MV) repair or prosthesis, is associated with clinical outcomes in patients with surgically treated MV disease. Methods: Among 750 patients who underwent MV surgery, we assessed LV-GLS by speckle tracking echocardiography in 344 patients (148 men, mean age 58±13 years) who showed preserved LV ejection fraction on echocardiography between 6 months and 2 years after MV surgery and who did not undergo aortic valve surgery. The assessed clinical events included admission for worsening of heart failure and cardiac death. Results: During a period of 42.4±26.0 months, 32 (9.3%) patients were hospitalized for worsening heart failure, and 3 (0.8%) died due to cardiac causes. The absolute value of LV-GLS (|LV-GLS|) was significantly lower in patients with clinical events than in those without (12.1±3.1 vs. 15.0±3.2%, p <0.001) despite comparable LV ejection fraction between groups. |LV-GLS| showed predictive value for clinical events (cut-off 13.9%, area under the curve 0.744, p<0.001). Patients with |LV-GLS| ≤14.0% had poorer outcomes than those with |LV-GLS| >14.0% (log-rank p <0.001). Prognosis was worse in patients with |LV-GLS| ≤14.0% and pulmonary hypertension than among those who with |LV-GLS| ≤14.0% without pulmonary hypertension (log rank p<0.001). In nested Cox proportional hazard regression models, reduced |LV-GLS| was independently associated with the occurrence of clinical events. Conclusions: In patients with surgically treated MV and preserved LV ejection fraction, assessment of LV-GLS provides functional information associated with cardiovascular outcomes.